Dermatitis atópica del adulto: un desafío diagnóstico y terapéutico - Carvajal A., Daniela; Valenzuela A., Fernando; Fernández M., Javier; Zamudio M., Andrea (Revista Hospital Clínico Universidad de Chile, 2019)
Adult atopic dermatitis is a chronically recurring inflammatory dermatosis which presents in various forms. Some of these forms develop mostly in adults such as head and neck dermatitis and chronic hand eczema. Even though the diagnosis is clinical it frequently requires further investigations to exclude differential diagnosis. Once confirmed, it is crucial to classify its severity and exclude other comorbidities. Treatment includes general measures such as the use of emollients and soap substitutes which are applicable in all cases regardless of its severity. Other therapeutic options include topical corticosteroids, topical calcineurin inhibitors, phototherapy and immunosuppressants. Their use will depend on the degree of severity and specific characteristics of each individual. Newer biologics have proven to be a safe and effective alternative, and seem to be a promising option in cases of adult atopic dermatitis refractory to conventional treatments.